2002
DOI: 10.1021/jf011672r
|View full text |Cite
|
Sign up to set email alerts
|

“Untypical Aging Off-Flavor” in Wine:  Synthesis of Potential Degradation Compounds of Indole-3-acetic Acid and Kynurenine and Their Evaluation as Precursors of 2-Aminoacetophenone

Abstract: Kynurenine (1) and indole-3-acetic acid (2) are considered as potential precursors of 2-aminoacetophenone (3), which is regarded to be the aroma impact compound causing an "untypical aging off-flavor" (UTA) in Vitis vinifera wines. The mechanism of the formation of 3 was studied using model fermentation and model sulfuration media spiked with 1 or 2 as potential precursors. Possible degradation products such as kynurenamine (4) and kynurenic acid (5), or skatole (6), 2-oxoskatole (7), 2-formamidoacetophenone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…Sodium acetate-2-13 C, deuteroacetic acid, DHQ, and all other chemicals were from Sigma-Aldrich (Oakville, ON, Canada). N-Formylacetophenone was synthesised according to Hoenicke et al (2002).…”
Section: Methodsmentioning
confidence: 99%
“…Sodium acetate-2-13 C, deuteroacetic acid, DHQ, and all other chemicals were from Sigma-Aldrich (Oakville, ON, Canada). N-Formylacetophenone was synthesised according to Hoenicke et al (2002).…”
Section: Methodsmentioning
confidence: 99%
“…But, in light of the findings of Escudero et al (2002), namely that acetaldehyde does not seem to influence the oxidised aroma, this should be investigated further. Hoenicke et al (2002) showed that 2-amino-acetophenone, which imparts an untypical aged off-flavour (acacia, soapy) to wine, is formed via the intermediates 2-formamidoacetophenone and 3-(2-formylaminophenyl)-3-oxopropionic acid after oxidative degradation of indole-3-acetic acid. More research is necessary on wine parameters that affect white wine aroma in combination with O2, especially under South African conditions.…”
Section: Effect Of Oxygen On Wine Aromamentioning
confidence: 99%
“…In fermentation media containing IAA as in natural musts, however, l-kynurenine was ruled out as a precursor of AAP (Hoenicke et al 2002a). Under these conditions, IAA was considered the relevant precursor.…”
Section: Microbiological Formation Of Aapmentioning
confidence: 99%
“…As a consequence, for average concentrations of nonbound IAA in white wine of ~100 µg/L at the time point of sulfiting, the formation of sensorially relevant concentrations of greater than 1 µg/L AAP is possible within a few weeks after SO 2 addition. Intermediate products of the tryptophan metabolism other than IAA are far less able to produce AAP (Christoph et al 1998, Hoenicke et al 2002a.…”
Section: Metabolism Of the Precursor Iaamentioning
confidence: 99%
See 1 more Smart Citation